Induced sheath voltage in power cables: A review. (September 2016) - Shaban, M.; Salam, M.A.; Ang, S.P.; Voon, William
Abstract: This paper presents a review on analytical techniques used to calculate induced sheath voltage in metallic sheaths of underground cables and overhead lines. The main purpose of this paper is to re-examine the existing research with the prospect of identifying possible gaps and differences that exist in the different approaches used to calculate induced sheath voltage. The different aspects of research conducted on induced sheath voltage in cables and lines due to lightning or mutual effects have been examined. The findings indicate that when two parallel cables are fairly close together then the electromagnetic coupling effect between the adjacent cables is difficult to calculate. Therefore, this review not only describes the influence of the different arrangements of the cables but it also examines the distance between the cables to calculate their effect on the magnitude of induced sheath voltage. Comparative results of different arrangements of cables and bonding are also provided to show their effectiveness in a given scenario.